Análise filogenética do gênero Lissoscarta Stal, 1869 (Hemiptera: Cicadellidae: Cicadellinae) - Felix, Márcio Eduardo (1999)
The Neotropical genus Lissoscarta Stâl is composed of seven known species: L. beckeri Mejdalani & Felix, L. catutara Young, L. nipata Young, L. pebasensis Young, L. pereneensis Young, L. schlingeri Young, and L. vespiformis (Fabricius). These species are ve1y similar in terms of color and externai morphology and can be identified only through the study of the male genitalia. The members of this genus are apparently Batesian mimics of wasps of the tribe Epiponini (Vespidae: Polistinae). This case of mimicry involves morphological and behavioral features. A phylogenetic analysis of Lissoscarta (excluding L. pebasensis, known only from females) employing the methodology of Phylogenetic Systematics (cladistics) is presented in this study. The external morphology of Lissoscarta with regard to the characters employed in the analysis, as well as the morphology of the male genitalia and the coloration, is detailly described. The following outgroups were selected through the criterion of general similarity with the ingroup: Amblyscartidia albofasciata (Walker), Dilobopterus exaltatus (Fabricius), Dilobopterus trinotatus (Signoret), and Dilobopterus vicinus (Signoret). Only one unrooted diagram was obtained from the data matrix, which included 88 characters and ten species. The monophyletic condition of Lissoscarta is supported by sixteen synapomorphies. The monophyly of this genus, which was subjectively based on the uniformity and exclusiveness of the mimetic pattem of its species, is thus corroborated. One of the most conspicuous apomorphic features of Lissoscarta is the abdomen strongly constricted at the base (a unique aspect within the Cicadellini), which simulates the abdominal petiole of the wasps. Some mimicry-related features of Lissoscarta apparently originated in Dilobopterus Signoret. Severa] of these apomorphies are probably the result of gradual, morphologically directed transfonnations in the Dilobopterus-Lissoscarta lineage. Tirns, the Neotropical genus Dilobopterus, which has about 5 l species, may be a paraphyletic taxon. Lissoscarta is possibly a specialized lineage of this genus in which mimetic features have arisen. Characters from the male pygofer and from the aedeagus were the ones that contributed mostly to the obtained topology. TI1ese structures show a clear increase in morphological complexity that is characterized by the variability of shapes and development of processes. On the other hand, the characters from the externai morphology and from the coloration were more conservative in Lissoscarta. This aspect may be explained by the direct relationship of states of these characters with the composition of the aposematic mimetic signal to the predator. This signal has a high significance in fitness to the mimic, due to the reduction of the risk of predation.